THE USE OF “ROKOHUMIN” FOR QUERCUS ROBUR L. PLANTING MATERIAL GROWING - Danilenko, O. M.; Tarnopilsky, P. B.; Gladun, G. B.; Gupal, V. V.; Volkov, P. O.; Kosatiy, D. M.; Samoylov, P. V. (Forestry and Forest Melioration, 2018)
Introduction The most effective way to regulate the growth and development of seedlings is to use controlled and semi-controlled environment, in particular growing in containers, in a greenhouse and an open watering area using different ways to intensify growth regimes. The new amino-acid humate fertilizer “Rokohumin” produced by Rokosan (Slovenia) is widely used in European countries in agriculture and forestry. The key difference from the group of humic products is in the composition of the fertilizer itself, namely in substances and elements of mineral nutrition, as well as their ratio. It contains 13 % of humic acid, 4 % of total nitrogen (N), 9 % of total phosphorus (P2O5), 14 % of total potassium (K2O) and about 30 % of different amino acids, which should be an effective means for intensifying the cutting propagation. In addition, “Rokohumin” contains magnesium, calcium, sulfur, boron, zinc, copper and manganese in chelated form, that is, in the organo-mineral complex. As a result, the fertilizer provides a more intense integrated effect on plants as compared to other humic preparations. Materials and Methods For oak seedlings growing, cylindrical containers made of agrotextile were used with dimensions: H = 28 cm, D = 8 cm, with V = 1,4 dm?. The composition of the substrate to fill them was as follows: a mixture of dark gray medium loamy soil harvested in the conditions of fresh and moist fertile sites and the transitional milled peat in a ratio of 3:1. The experiment consisted of four variants: control, where seedlings were grown without fertilizer, two variants using “Rhokhumin” at concentrations of 10 and 20 ml ? l-1 for soil dressing with a consumption rate of 10 liters per 1 m? and a variant of foliar dressing with a concentration of fertilizer solution of 10 ml ? l-1. Triple fertilizing was carried out during the growing season: the first – after the mass emergence of seedlings; the second – after the true oak leaf appearance; the third – in the period of intense growth of seedlings. Analysis of field research data was performed using variation statistics methods. Results The study of fertilizer impact on the growth of containerized oak seedlings (Quercus robur L.) was carried out in the greenhouse seedling unit of the Pivdenne Forestry Breeding and Seed Complex of the Kharkiv Forest Research Station in 2016 in the following directions: studying the growth and development of oak seedlings of English oak depending on methods of fertilizer treatment and apparent concentrations and doses of the amino acid humate fertilizer in an open area with irrigation. The effectiveness of the fertilizer depends on the input method and concentration of working solutions. The maximum effect on the growth of height and root collar diameter and on increase of air-dry weight of aboveground and underground parts of seedlings was obtained in a variant with fertilizer solution concentration of 20 ml ? l-1. In this version, the average height of seedlings is bigger by 81 %, the diameter by 42 %, the mass of aboveground and underground parts by 68 % and 27 %, respectively. Leaf feeding with fertilizer solution of 10 ml ? l-1 has contributed to more active growth in height by 45 % and increase the weight of aboveground parts by 25 %. Leaf feeding did not affect root weight. Conclusions The use of “Rokohumin” gives an opportunity to obtain planting material with given sizes, including large-sized, for use not only in silvicultural work but in horticulture.